2008
DOI: 10.1111/j.1439-0388.2007.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

QTL detection for milk production traits in goats using a longitudinal model

Abstract: Eight paternal half-sib families were used to identify chromosomal regions associated with variation in the lactation curves of dairy goats. DNA samples from 162 animals were amplified by PCR for 37 microsatellite markers, from Capra hircus autosomes CHI3, CHI6, CHI14 and CHI20. Milk samples were collected during 6 years, and there were 897 records for milk yield (MY) and 814 for fat (FP) and protein percentage (PP). The analysis was conducted in two stages. First, a random regression model with several fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Polymorphisms in the goat PRNP gene have been associated with susceptibility to scrapie in different breeds [14]. Few other studies reported QTL for milk and fleece production traits and disease resistance [15-20]. Investigations of genes affecting coat colour identified polymorphisms associated with this phenotypic trait [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in the goat PRNP gene have been associated with susceptibility to scrapie in different breeds [14]. Few other studies reported QTL for milk and fleece production traits and disease resistance [15-20]. Investigations of genes affecting coat colour identified polymorphisms associated with this phenotypic trait [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used by Roldán et al (2008) to detect QTL for milk production traits using a longitudinal model identified nine map positions affecting any parameter of the lactation function of dairy goats: one in CHI3, four in CHI6, two in CHI14 and two in CHI20. Some of these results were consistent with QTLs found in dairy cattle while using either aggregate lactation records, or longitudinal-linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Roldán et al (2008) identified chromosomal regions associated with variation in the lactation function of goats using the two-stage procedure as employed by Rodriguez-Zas et al (2002).…”
Section: Qtl Detection For Milk Production Traits In Goatsmentioning
confidence: 99%
“…While dense quantitative trait loci (QTL) maps of dairy traits have been obtained in cattle and sheep, a single partial genome scan for milk yield and fat and protein contents has been performed so far (Roldán et al 2008). However, many of the findings obtained in cattle can be probably extrapolated to goats, so they will be commented in the following paragraphs.…”
Section: Genomic Architecture Of Protein and Lipid Phenotypes In Goatmentioning
confidence: 99%